BOOK NOTICES / BOEKAANKONDIGINGS - Lategan, Bernard C. (Scriptura, 1987)
Carlisle, Thomas John 1986. Beginning with Mary. Women of the Gospels in portrait. Grand Rapids: Eerdmans.White, Ronald C, Jr, Weeks, Louis B, & Rosell, Garth M (eds) 1986. American Christianity. A case approach. Grand Rapids: Eerdmans.Kannengiesser, Charles (ed) 1986. Early Christian spirituality. Translated by Pamela Bright. Philadelphia: Fortress Press.Stretch, Lewis 1986. Engineering: mechanical or moral science? Oxford: Becket Publications.Du Plessis, A J, van Wyk, JH, Botha, J, Venter, J J, & Rabali, TC, Eloff, T 1987. ‘n Reformatoriese kommentaar op die Kairos-dokument. Potchefstroom: Die PU vir CHO, Instituut vir Reformatoriese Studie.Klay, Robin Kendrick 1986. Counting the cost: the economics of Christian stewardship. Grand Rapids: Eerdmans.Neuhaus, Richard John (ed) 1986. Confession, conflict & community. Grand Rapids: Eerdmans.Lammers, Stephen E & Verhey, Allen (eds) 1987. On moral medicine. Theological perspectives in medical ethics. Grand Rapids: Eerdmans.Kretzchmar, Louise 1986. The voice of Black Theology in South Africa. Johannesburg: Ravan Press.Marais, J C 1986. Die NG Kerk en die regverdiging van apartheid. Sovenga: Stofberg Teologiese Skool.McKeating, Henry 1986 (2nd imp). Living with guilt. London: SCM Press.Lake, Frank 1986. Clinical theology. A theological and psychological basis to clinical pastoral care (Abridged by Martin H Yeomans.) London: Darton, Longman & Todd.Hexman, Irving & Poewe, Karla 1986. Understanding cults and new religions. Grand Rapids: Eerdmans.Kingsbury, Jack Dean 1986. Matthew. Philadelphia: Fortress Press.Neusner, Jacob 1986. Judaism in the matrix of Christianity. Philadelphia: Fortress Press.McCarter, P Kyle Jr 1986. Textual criticism. Recovering the text of the Hebrew Bible. Philadelphia: Fortress Press.Hinson, E Glenn (Tr/ed) 1986. Understanding of the church. Philadelphia: Fortress Press.Branson, mark Lau & Padilla, C René (eds) 1986. Conflict and context. Hermeneutics in the Americas. Grand Rapids: Eerdmans.McKim, Donald (ed) 1986. How Karl Barth changed my mind. Grand Rapids: Eerdmans.McKim, Donald (ed) 1986. A guide to contemporary hermeneutics. Major trends in biblical interpretation. Grand Rapids: Eerdmans.Berkhof, Hendrikus 1986. Christian faith. An introduction to the study of the faith. Translated by Sierd Woudstra. Grand Rapids: Eerdmans.